A revision of the genera Pseudosmittia Edwards, 1932, Allocladius Kieffer, 1913, and Hydrosmittia gen. n. (Diptera: Chironomidae, Orthocladiinae) - Ferrington Jr., Leonardo C.; Sæther, Ole A. (Zootaxa, 2011)
The genera Pseudosmittia Edwards, 1932, and Allocladius Kieffer, 1913, supported by parsimony analysis, can be divided into three groups, Pseudosmittia, Allocladius and Hydrosmittia gen. n. Generic diagnoses to all stages and both sexes of all three genera are given. The mostly Neotropical and Afrotropical Allocladius together with the mostly Holarctic and Afrotropical Hydrosmittia form the sister group of the more widespread Pseudosmittia. Allocladius in addition to some basal species is divided into a paraphyletic nearly Cosmopolitan fortispinatus group, a monotypic Afrotropical soemmei group, an Afrotropical and Palaearctic niger group, a Holarctic nanseni group, and a Neotropical, Afrotropical and Holarctic longicrus group; Hydrosmittia into an Afrotropical and Palaearctic brevicornis group and a mostly Holarctic ruttneri group. Pseudosmittia is divided into 13 species groups in phyletic sequence: gracilis [simplex + rotunda (topei (digitata (xanthostola + brachydicrana + insulsa)], [conjuncta (tokaraneoa + albipennis (brevifurcata (angusta group, divided into angusta, trilobata, lamasi, danconai, uncata and forcipata subgroups)]. The xanthostola and brachydicrana groups are with few exceptions known only from South Asia and the Indo-Pacific region, while most other groups are present in most regions.        Keys to male and female imagines, pupae and larvae of all three genera are given. Type material of 180 species assigned to Pseudosmittia, Camptocladius v. d. Wulp, Spaniotoma Philippi, Smittia Holmgren, Mesosmittia Brundin, Orthosmittia Goetghebuer, Ancylocladius Sublette et Wirth, Allocladius Kieffer, and Lindebergia Tuiskunen, belonging to 15 museums have been re-examined, lectotypes designated, and new combinations and synonyms given. An additional 21 species are lost or could not be located, of these 5 are declared nomina dubia. Another 4 species were not available for study or not examined. Most of these could be placed in other genera or as synonyms of species in Pseudosmittia. One hundred and thirty species are treated, 37 of which are new, 93 species are completely redescribed in all available stages. The following new species are described: Allocladius bubatus, A. caspersi, A. deborae, A. hirticaudatus, A. luciniolus, A. soemmei, A. wangorum, Hydrosmittia aagaardi, H. annulata, H. falsicostata, H. soelii, H. tenuistylata, Pseudosmittia aculeathrix, P. acutilobata, P. carita, P. christmasensis, P. cristagata, P. cunealata, P. dolabrata, P. digitrienta, P. fusata, P. laticauda, P. legonensis, P. licina, P. longicornia, P. malickyi, P. navama, P. parifusata, P. parinavama, P. pedata, P. propetropis, P. pugnata, P. siamensis, P. spinispinata, P. tericristata, P. tokunagai, and P. unniae. Ten species of Allocladius (including 2 parthenogenetic), 4 species of Hydrosmittia (including 2 parthenogenetic), and 31 species of Pseudosmittia (including 3 parthenogenetic and 3 species known only from females) are known as female imagines; 5 species of Allocladius, 6 species of Hydrosmittia and 12 species of Pseudosmittia are known as pupae; and 4 species of Allocladius, 5 species of Hydrosmittia and 10 species of Pseudosmittia are known as larvae.        Errors in previous publications are corrected and remarks on variation given. The genera treated contain at least 7 apparently obligate parthenogenetic species, while facultative parthenogenesis is found in at least one species and may be widespread.        The species of Hydrosmittia probably all are truly aquatic, while Allocladius has species found in both fully aquatic environments and in moist earth. In Pseudosmittia there are no certain fully aquatic species. Most species appear to be semiaquatic to semiterrestrial or live in the marine intertidal zone. The insulsa, brachydicrana, and xanthostola groups contain mostly marine seashore species, and several groups have species, which larvae live both in semiaquatic freshwater localities and on the seashore. In the angusta group, however, only P. bifurcata appears to be intertidal.Only in Allocladius a cool southern transantarctic Gondwanian vicariance may have taken place, but combined with dispersal to West Asia, further to the Euro-Mediterranean and East Asian Regions, and across a Beringian Region to North America. A more northern warm Gondwanian connection between West Africa and East South America could be present but not common in Pseudosmittia. The dominating distribution pattern in Pseudosmittia appear to be caused by direct dispersal, in America across the Caribbean and the Central American lowland, in the Indian Ocean and the Pacific across oceans by floating debris and vegetation.